2019
DOI: 10.1002/anie.201902987
|View full text |Cite
|
Sign up to set email alerts
|

Direct Monitoring of Cell Membrane Vesiculation with 2D AuNP@MnO2 Nanosheet Supraparticles at the Single‐Particle Level

Abstract: We herein demonstrate robust two‐dimensional (2D) UFO‐shaped plasmonic supraparticles made of gold nanoparticles (AuNPs) and MnO2 nanosheets (denoted as AMNS‐SPs) for directly monitoring cell membrane vesiculation at the single‐particle level. Because the decorated MnO2 nanosheets are ultrathin (4.2 nm) and have large diameters (230 nm), they are flexible enough for deformation and folding for parceling of the AuNPs during the endocytosis process. Correspondingly, the surrounding refractive index of the AuNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…Then, dark-field optical microscope (DFM) was used to characterize the scattering feature of these particles at the single-particle level. 9,12,[33][34][35][36][37][38] As shown in Figure 1d, all of the AuCMs disperse separately with uniform and characteristic green color. However, for the AuCDs, noticeable red-shift in the dark-field image can be observed after the dimerization process (Figure 1g).…”
Section: Spectroscopic and Microscopic Characterizations Of Aucms Andmentioning
confidence: 92%
“…Then, dark-field optical microscope (DFM) was used to characterize the scattering feature of these particles at the single-particle level. 9,12,[33][34][35][36][37][38] As shown in Figure 1d, all of the AuCMs disperse separately with uniform and characteristic green color. However, for the AuCDs, noticeable red-shift in the dark-field image can be observed after the dimerization process (Figure 1g).…”
Section: Spectroscopic and Microscopic Characterizations Of Aucms Andmentioning
confidence: 92%
“…A recent study reported UFO‐shaped Au@MnO 2 was utilized for monitoring cell membrane vesiculation directly at the single‐particle level by Xia group ( Figure ) . In this article, MnO 2 NSs are capable of deformation and folding during the endocytosis process thanks to ultrathin structures with large diameters, which further affects the surrounding refractive index of the Au NPs, and thus results in a distinct shift of the localized surface plasmon resonance (LSPR).…”
Section: Diagnostic Applicationsmentioning
confidence: 97%
“…Au@MnO 2 for monitoring of cell membrane vesiculation. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ling and coworkers demonstrated 2D UFO‐shaped plasmonic supraparticles constructed by AuNPs and MnO 2 nanosheets (denoted as AMNS‐SPs) to directly monitor cell membrane vesiculation at the single‐particle level (Figure 12C). [ 250 ] The AMNS‐SPs were flexible enough for deformation and folding during the endocytosis process, which was identified by the distinct red‐shift of the Rayleigh scattering spectra. Due to the presence of the reducing molecules in cells, the surrounding MnO 2 nanosheets could be etched, which would cause the blue‐shift in the scattering spectra of AMNS‐SPs, providing a direct criterion to distinguish the completion of cell membrane engulfment process.…”
Section: Single Plasmonic Nanoprobes In Cell Imagingmentioning
confidence: 99%